Risk Management in High-Conflict Divorce/Parenting Referrals: It’s How You Walk Through the Fire - Amundson, Jon K.; Lux, Glenda M. (Canadian Journal of Counselling and Psychotherapy, 2016)
Professionals involved in counselling and psychotherapy will find themselves confronted by the problems associated with high-conflict parenting (HCP) after relationship dissolution. With these cases come unique challenges. Issues related to risk management and effective service delivery need to be considered. This article provides an introduction to professional issues related to HCP and ways to negotiate these challenging cases.